Pembatalan Putusan Arbitrase Internasional Antara Hukum Indonesia Dan Malaysia Harmonisasinya Dengan Hukum Model Uncitral - Sudarna, Sudarna (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
The rapid development of international business can drive good economic growth for a country; on the other hand, the potential for business disputes is also increasing. One of the legal instruments used by subjects of international law is arbitration, whether established by international institutions or states. To conduct international arbitration, it should be under the framework or scheme of international arbitration. The purpose of this research is to compare Indonesian arbitration law with Malaysian arbitration law, which has been adjusted to the framework or scheme of international arbitration. The research results show that Malaysian arbitration law, as regulated in Arbitration Law Number 646 of 2005, is more in line with the international arbitration scheme except in the matter of annulment of international arbitration awards, while Indonesian arbitration law, as regulated in Law Number 30 of 1999, is not yet in line with the international arbitration scheme. Based on this reality, changes are needed to Law Number 30 of 1999, specifically the formation of a law that regulates arbitration and is in line with the framework or scheme of international arbitration.